PENGARUH PERGAULAN TEMAN SEBAYA DAN GAYA HIDUP TERADAP PERILAKU KONSUMTIF MAHASISWA PENDIDIKAN EKONOMI SEMESTER VIII UNIVERSITAS BHINNEKA PGRI TAHUN AKADEMIK 2019/2020 - Nana Widayanti; Maria Agatha Sri (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2021)
ABSTRACT Widayanti, Nana. 2020. Effects of Peer Intercourse and Lifestyle on Consumer Consumptive Behavior of Semester Economic Education VIII UNIVERSITY OF BHINNEKA PGRI Academic Year 2019/2020. Essay Economic Education. UNIVERSITY BHINNEKA PGRI. Advisor: Maria Agatha S W, M.Pd., M.M Peer association is life side by side with people that are around us that affect out lives and have is positive impacts such as students studying together or doing other benefical and negative activities such as carrying out economic activities tend to behave consumptive. Whereas lifestyle is a way someone spends the time and the use of money owned, shared students who are not able to control lifestyle and have relationship negative peers so they only think of momentary pleasures and unable to distinguish between needs and desires because of that classified in consumptive behavior for the sake of paralleling or aligning the situation with these peers. This research aims to analyze the effect of peer relationship and lifestyle on behavior consumptive economic education students VIII semester UNIVERSITY BHINNEKA PGRI Academic Year 2019/2020 Data collection method in this research is using a questionnaire. The research method uses multiple linier regression analysis. (Test) proven peer association value t count (4,435) > t table (2,017), lifestyle t value (3,435)> t table (2,017) can be concluded partially